2020
DOI: 10.3389/fcell.2020.00278
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0000848 Promotes Trophoblast Cell Migration and Invasion and Inhibits Cell Apoptosis by Sponging hsa-miR-6768-5p

Abstract: Background: Fetal growth restriction (FGR) is a worldwide problem, and a major cause of perinatal morbidity. The precise molecular mechanisms involved in placental development and function during FGR remain poorly understood. Circular RNAs (circRNAs) are important biological molecules associated with disease pathogenesis. However, the role of circRNAs in FGR has not been well studied. Methods: circRNA expression profiles in placental tissues with and without FGR were identified by circRNA microarray. circRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Therefore, the changes of total protein and phosphorylated protein levels of PI3K and Akt were detected by silencing or overexpressing circRNA and miRNA. In fact, many studies on the circRNA pathway have adopted this approach, that is, the expression of the terminal pathway was verified by regulating the circRNA/miRNA/mRNA axis ( Luo et al, 2020 ; Wang et al, 2020a ). Taken together, this evidence supported that PI3K/Akt signaling pathway functioned in accelerating full-thickness wound healing and attenuating keloid formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the changes of total protein and phosphorylated protein levels of PI3K and Akt were detected by silencing or overexpressing circRNA and miRNA. In fact, many studies on the circRNA pathway have adopted this approach, that is, the expression of the terminal pathway was verified by regulating the circRNA/miRNA/mRNA axis ( Luo et al, 2020 ; Wang et al, 2020a ). Taken together, this evidence supported that PI3K/Akt signaling pathway functioned in accelerating full-thickness wound healing and attenuating keloid formation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs have been manifested not to be the transcriptional noise, and but to be the important regulatory molecules ( Zhuang et al, 2015 ; Chen et al, 2016 , 2017 ; Li et al, 2016a , b ; Tran et al, 2020 ), and circRNAs are novel endogenous non-coding RNAs that have been identified as owing key regulatory roles in the cancer biology ( Ma et al, 2019 ; Di Agostino et al, 2020 ; Dong et al, 2020 ; Jin et al, 2020 ; Li and Wang, 2020 ; Liu et al, 2020 ; Ou et al, 2020 ; Zhang et al, 2020a ). circRNAs act as important roles in the development and progression of cancers and are involved in various biological processes, such as cell proliferation, apoptosis, and migration by regulating gene expression ( Liu et al, 2019 ; Di Agostino et al, 2020 ; Ji et al, 2020 ; Tang and Chen, 2020 ; Wang et al, 2020c ). Mangy circRNAs have been reported to play important functions in cervical cancers, such as hsa_circ_0000515 ( Tang and Chen, 2020 ), has_ circ_0000388 ( Meng et al, 2020 ), circ-HIPK3 ( Qian and Huang, 2020 ), circ-ITCH ( Li et al, 2020 ; Wu et al, 2020b ), circCLK3 ( Jin et al, 2020 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-seven pregnant women with FGR and thirty seven healthy pregnant women enrolled in this study were the same as the participants in our previous study [7]. Their detailed characteristics have been reported in our previous study.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…After 24 h of transfection, the Transwell assays were performed to examine the migration and invasion capabilities of the indicated groups using the same method as described in our previous study [7]. The migrated or invaded cells at the bottom of the lter membrane were photographed using a light microscope (Nikon, Tokyo, Japan) at 200X magni cation.…”
Section: Transwell Assay and Ow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation